Towards Understanding the Firm Specific Determinants of Corporate Financial Flexibility - Almomani, Mohammad Abdullah; Obeidat, Mohammed Ibrahim Sultan; Al-Athamneh, Mustafa; Almomani, Tareq Mohammad; Darkel, Nadeen Mohammed Adnan M.Y (International Journal of Economics and Financial Issues, 2024)
The study objects for determining the most important firm specific factors affecting the corporate financial flexibility of the listed manufacturing firms at Amman Stock Exchange. Firm specific factors including, profitability, assets tangibility, cash holdings, and retained earnings, are taken into consideration, as possible internal determinants of corporate financial flexibility. To achieve the objectives of the study, secondary data covering the period 2013-2021, of 40 listed manufacturing listed firms at Amman Stock Exchange, had been collected and used in the analysis and hypotheses testing. Employing both of the simple and linear regression methods in hypotheses testing, and at the individual level of independent variables, the result reveals a significant impact of profitability, assets tangibility, cash holdings, and capital structure, and insignificant impact of retained earnings, on corporate financial flexibility. Moreover, a combined grouping significant impact, the result shows for the different firm specific factors, as a single group, on financial flexibility. The study recommends more investigations regarding financial flexibility and its internal and external macroeconomic determinants.